The Effect of Work Stress and Workload on Turnover Intention with Job Satisfaction as a Mediation Variable on Employees of Bank Indonesia Purwokerto Representative - Achmad Fasichulisani; Lie Liana (Eduvest - Journal of Universal Studies, 2026)
The phenomenon of turnover intention has become a strategic issue in human resource management, including in the Bank Indonesia Purwokerto Representative environment. This research aims to test the influence of work stress and workload on turnover intention, with job satisfaction as a mediation variable. The research method used is quantitative, employing a survey approach and using a questionnaire as the data collection instrument. The study population consists of all employees of Bank Indonesia Purwokerto, with a purposive sampling technique based on a minimum work period of more than one year. Data analysis was carried out using descriptive tests, validity tests, reliability tests, F-tests, t-tests, and Sobel tests to examine the mediation effect. The research results show that work stress and workload have a significant negative effect on job satisfaction. Furthermore, work stress and workload also have a significant positive effect on turnover intention. In addition, job satisfaction was proven to mediate the influence of work stress and workload on turnover intention. These findings provide practical implications for Bank Indonesia management to monitor the levels of stress and workload and to enhance job satisfaction among employees to reduce turnover intention.